2020
DOI: 10.1177/0268355520936420
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing the risk of venous thromboembolism following superficial endovenous treatment: A UK and Republic of Ireland consensus study

Abstract: Objectives Venous thromboembolism is a potentially fatal complication of superficial endovenous treatment. Proper risk assessment and thromboprophylaxis could mitigate this hazard; however, there are currently no evidence-based or consensus guidelines. This study surveyed UK and Republic of Ireland vascular consultants to determine areas of consensus. Methods A 32-item survey was sent to vascular consultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
1
17
0
4
Order By: Relevance
“…Currently, there is not solid evidence-based justification, but a recent consensus in UK and Ireland concluded that prophylaxis with low-molecular-weight heparin following superficial endovenous treatment is recommended. 29…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is not solid evidence-based justification, but a recent consensus in UK and Ireland concluded that prophylaxis with low-molecular-weight heparin following superficial endovenous treatment is recommended. 29…”
Section: Discussionmentioning
confidence: 99%
“…Practice varies greatly for low risk patients, ranging from never giving prophylaxis; to using a single or multiple doses of LMWH depending on the perception of the patient and clinicians' individual preferences. 2 There is no good evidence for any of these practices and this is likely to remain the case because of the very low incidence of VTE in this patient group. Because these are not the patients of primary concern the RSMVF Advice simply includes the regimes that are commonly used.…”
mentioning
confidence: 94%
“…The Advice specifies three levels of risk for patients – low risk patients, for whom no good evidence exists to guide practice; high risk patients, who should receive prophylaxis because of their obvious risk factors; and an intermediate group at “additional risk”, who probably should receive adequate pharmacological prophylaxis but commonly do not. 2 For both of the latter groups, the Advice recommends more prolonged prophylaxis than that typically used by many clinicians.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Por exemplo, na UTI a incidência de TVP é de 29-31% sem profilaxia e de 12% com profilaxia adequada. 2,5 Como a TEP fatal pode ser a primeira manifestação clínica, é inapropriado aguardar o aparecimento de sintomas para diagnosticar e tratar um episódio de TEV. Além disso, a detecção da TVP pode ser difícil, já que apenas cerca da metade dos pacientes tem quadro clínico evidente.…”
Section: Introductionunclassified